Skip to content
Related Articles

Related Articles

ISRO | ISRO CS 2007 | Question 1
  • Last Updated : 20 Nov, 2018

The Boolean expression Y = (A + B’ + A’B)C’ is given by
(A) AC’
(B) BC’
(C) C’
(D) AB


Answer: (C)

Explanation:

Y = (A + B' + A'B)C'
Y = AC' + B'C' + A'BC'
Y = (A + A'B)C' + B'C'
Y = (A + B)C' + B'C'
Y = AC' + BC' + B'C'
Y = AC' + C'(B + B') // B + B' = 1
Y = AC' + C'
Y = C'

So, option (C) is correct.

Quiz of this Question

My Personal Notes arrow_drop_up
Recommended Articles
Page :